GABAergic dysfunction in postmortem dorsolateral prefrontal cortex: implications for cognitive deficits in schizophrenia and affective disorders - Hughes, Hannah; Brady, Lillian J.; Schoonover, Kirsten E. (Frontiers in Cellular Neuroscience, 2024)
The microcircuitry within superficial layers of the dorsolateral prefrontal cortex (DLPFC), composed of excitatory pyramidal neurons and inhibitory GABAergic interneurons, has been suggested as the neural substrate of working memory performance. In schizophrenia, working memory impairments are thought to result from alterations of microcircuitry within the DLPFC. GABAergic interneurons, in particular, are crucially involved in synchronizing neural activity at gamma frequency, the power of which increases with working memory load. Alterations of GABAergic interneurons, particularly parvalbumin (PV) and somatostatin (SST) subtypes, are frequently observed in schizophrenia. Abnormalities of GABAergic neurotransmission, such as deficiencies in the 67 kDA isoform of GABA synthesis enzyme (GAD67), vesicular GABA transporter (vGAT), and GABA reuptake transporter 1 (GAT1) in presynaptic boutons, as well as postsynaptic alterations in GABAA receptor subunits further contribute to impaired inhibition. This review explores GABAergic abnormalities of the postmortem DLPFC in schizophrenia, with a focus on the roles of interneuron subtypes involved in cognition, and GABAergic neurotransmission within presynaptic boutons and postsynaptic alterations. Where available, comparisons between schizophrenia and affective disorders that share cognitive pathology such as bipolar disorder and major depressive disorder will be made. Challenges in directly measuring GABA levels are addressed, emphasizing the need for innovative techniques. Understanding GABAergic abnormalities and their implications for neural circuit dysfunction in schizophrenia is crucial for developing targeted therapies.